SIMULAKRA SECOND ACCOUNT INSTAGRAM FOR FKIP UNTIRTA STUDENTS - wendy, Liyola (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2024)
Students are people who are easily influenced by popular culture. Students in their daily lives are inseparable from the lifestyle that is uploaded and thoroughly documented on their personal Instagram account. The lifestyle that is followed is based on the times, such as consumption in visiting cafes/malls, buying beauty/skincare products that are influenced by advertisements/beauty vloggers, and fashion trends. So that what is bought and done is based on the sign, prestige, luxury or satisfaction that is felt.In examining the existing problems, researchers used qualitative research with a descriptive approach. This research was conducted at FKIP Untirta with subjects namely FKIP Untirta students. Data collection techniques were carried out by observation, interview and documentation methods. From the research that the researchers have done, the results of the study show that students pack their Instagram account with "aesthetic" in the hope that the individual will get social status and meaning. This makes what is consumed also have a certain code or meaning. So that Instagram social media becomes a place for the simulation to work. Then there is a new phenomenon in Instagram social media, namely the presence of second accounts. The reasons students use the second account are conflicts in the first account, feeling bored and bored, not wanting to spoil the aesthetics of the first account, as the most comfortable space for those closest to them, to find out about other things, and to keep archives of memories.